2011
DOI: 10.1103/physrevb.84.144415
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural phase transitions in erbium at low temperatures and high pressures

Abstract: Electrical resistance and crystal structure measurements have been carried out on polycrystalline erbium (Er) at temperatures down to 10 K and pressures up to 20 GPa. An abrupt change in the slope of the resistance is observed with decreasing temperature below 84 K which is associated with the c-axis modulated antiferromagnetic (AFM) ordering of the Er moments. With increasing pressure, the temperature of the resistance slope change and the corresponding AFM ordering temperature decrease until vanishing above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The disappearance of the antiferromagnetic ordering occurring in the same 7-9 GPa pressure range as the crystalline structure transition of Ho from the hcp to α-Sm-type structure [17,18] suggested that the disappearance of the AFM phase might result from the crystalline structure transformation. This conjecture was further supported by the very recent study of the structure and resistance properties of erbium at high pressures in which a transformation to the α-Sm structure was also accompanied by a loss of magnetic order [19]. The previous electrical resistance investigations at ambient pressure have been shown to be a reliable technique for determining the temperature of the transition from the paramagnetic to helical antiferromagnetic state for rare earth metals.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The disappearance of the antiferromagnetic ordering occurring in the same 7-9 GPa pressure range as the crystalline structure transition of Ho from the hcp to α-Sm-type structure [17,18] suggested that the disappearance of the AFM phase might result from the crystalline structure transformation. This conjecture was further supported by the very recent study of the structure and resistance properties of erbium at high pressures in which a transformation to the α-Sm structure was also accompanied by a loss of magnetic order [19]. The previous electrical resistance investigations at ambient pressure have been shown to be a reliable technique for determining the temperature of the transition from the paramagnetic to helical antiferromagnetic state for rare earth metals.…”
Section: Introductionmentioning
confidence: 69%
“…Resistance measured in the basal plane, however, is affected only minimally [23][24][25] by this effect. For polycrystalline samples, the resistance should be an admixture of the c-axis and basal plane resistances which would result in a small, but discernible, upturn in the resistance at T N [19]. However, uniaxial compression of a polycrystalline sample could lead to a preferred orientation in the sample (c-axis orientation along the compression direction in the diamond anvil cell) such that the measured resistance is predominantly from the basal plane resistance behavior as observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic properties evolution with structural transformations for the six 4 f FM metals were investigated by magnetic measurements (Gd-Ho [11][12][13], Gd [14], and Gd-Tm [15]), electrical resistance measurements (Gd [16][17][18], Tb [18][19][20], Dy [17,18,21], and Er [22,23]), neutron diffraction (Gd [24], Tb [19,[25][26][27], Dy [28,29], and Ho [30,31]), Mössbauer spectroscopy (Dy [32]), and x-ray absorption near the edge structure (Dy [32]).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive understanding of the magnetostructural correlation in a series of six 4 f FM metals Gd-Tm is very important to discuss the connection between ferromagnetism and metallicity. Given this background, the only available experimental data for Er and Tm are on ac magnetic susceptibility (Er [15], Tm [15]) and electrical resistivity (Er [22,23]), and there have been no reports on more reliable magnetization using a SQUID. Thus, in the present study, to comprehend the universal trend in the pressure effects on six 4 f FM metals, the ac magnetization under pressure for Er and Tm has been measured using a SQUID magnetometer, which corresponds to the type (iii) measurement mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic ordering transitions in heavy lanthanides have been studied by magnetic susceptibility measurements in a diamond anvil cell up to modest pressure of 10-20 GPa and a systematic decrease in magnetic ordering temperature with increasing pressure has been documented [4]. However, recent introduction of ultrasensitive electrical transport measurements to higher pressures have extended magnetic ordering temperature measurements in lanthanides to ultra-high pressures [5][6][7]. The initial decrease in magnetic ordering temperature is followed by a rapid increase in magnetic ordering temperatures as documented in heavy lanthanide metal like dysprosium [6,7].…”
Section: Introductionmentioning
confidence: 99%